Risk analysis of hydroelectric power station considering identified risk factors based on condition distress rating - Usman F.; Banuar N. (Asian Research Publishing Network, 2023)
Hydroelectric power plant and its infrastructure are very strategic asset to the Nation in providing their services. This study is aimed to analyze the risk associated with structural stability of shotcrete lining on the tunnel and cavern of SIP hydroelectric power station while taking into account its risk factors. Prior to conducting risk analysis, level of distress rating for every chain age were determined to be considered together. These risks are then analyzed with considering other significant risk factors by quantifying its impact and probability for each risk to generate condition risk for the tunnels and cavern. From this study, by implementing risk analysis in determining condition of shotcrete lining of the tunnel and cavern, the severity of any particular area is defined more precise. The results discovered that the value of risks were identified ranging from 0.05 to 10.08. The highest risk value of 10.08 was discovered at the west wall of the cavern is due to the fact that cavern possess higher assets value need to be preserved. It is concluded that the results from the risk analysis provided more accurate estimation on preventive maintenance and remedial action depending on the operational purposes of the tunnel compared to the individual condition rating without the implementation of risk analysis. 2006-2017 Asian Research Publishing Network (ARPN). All rights reserved.